Kewenangan Jaksa dalam Melakukan Perampasan Aset Terdakwa Korupsi - Irawan, Chandra; Sirozi, M.; SA, Romli; Kencana, Ulya (Wajah Hukum, 2023)
Research on the authority of prosecutors in confiscating assets of corruption defendants, because returning state assets to Corruption Eradication is difficult. In fact, corruption causes a lot of losses to the country. Even though criminal procedures have been made to save state assets, but it hasn't worked yet. Therefore, returning the assets of Corruption perpetrators can save state assets. The authority of the Prosecutor's Office plays a very important role in this effort. Research problems regarding the authority of prosecutors in confiscating assets of corruption defendants, the authority of the Prosecutor's Office to address the issue of returning state assets. Legal research method with a statutory approach. The result is that after the Corruption Eradication results there is a return of state assets, namely, there is a court decision. The legal basis for return is stated in Article 18 UU.31/1999 jo UU. 20/2001 Corruption Crimes, by summoning the convict, family and legal advisors by the Prosecutor regarding the stages, implementation of the return.